2022
DOI: 10.1016/j.genhosppsych.2021.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Distinct psycho-oncological support inclinations and needs in patients with cancer: A large sample latent class analysis approach

Abstract: Background In patients with cancer, the routine recording of distress symptoms has been widely established in recent years. Psycho-oncological support has proven to reduce distress and increase quality of life. Despite high levels of distress as well as physical and emotional challenges in patients with cancer, a significant proportion forgoes psycho-oncological services. Methods A cross-sectional retrospective evaluation was carried out. Latent class analysis was used to examine the relationship between distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The existing literature suggests that especially oncologists who skillfully recommend PO might improve patients’ uptake of those services (Swiss study) [ 60 ]. Additionally, the identification of specific subgroups of cancer patients with different distress profiles might contribute to a more tailored treatment offer (Swiss study) [ 61 ] reducing the gap between distress and the request for PO.…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature suggests that especially oncologists who skillfully recommend PO might improve patients’ uptake of those services (Swiss study) [ 60 ]. Additionally, the identification of specific subgroups of cancer patients with different distress profiles might contribute to a more tailored treatment offer (Swiss study) [ 61 ] reducing the gap between distress and the request for PO.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from socio-demographic aspects ( Schulze et al, 2022a ), there are recurrent psychosocial aspects, some influenced by socio-demographic ones (such as cultural beliefs and stigma regarding mental health services and problems), that need to be addressed; several patients, for example, report thinking psychological support is not necessary or useful for their perceived level of distress, or that their level of distress is not severe enough to warrant intervention, hence preferring self-help ( Clover et al, 2015 ). In addition, Schulze et al (2022b) found that high emotional distress (but not physical) acts as a barrier to the utilisation of psycho-oncological support, yet, it appears that only suffering from both emotional and physical distress leads to the wish for support ( Schulze et al, 2022b ).…”
Section: Barriers To the Use Of Psycho-oncological Supportmentioning
confidence: 99%
“…Prospective studies should consider exploring individual profiles of ICD patients to identify subgroups most vulnerable to the pandemic. Novel approaches, such as a latent class analysis, might be suited for the identification of specific subgroups [45]. Although a history of COVID-19 of closely related persons, such as family, friends and partners, did not predict anxiety, depression or PTSD in ICD patients, future research might want to extend analyses regarding further COVID-19-related variables, which might be linked to those psychiatric symptoms or disorders.…”
Section: Limitations and Future Researchmentioning
confidence: 99%